Entrepreneurship Gender, Geographies and Social Context - Burger-Helmchen, Thierry (IntechOpen, 2012)
Entrepreneurship is a main driver of economic growth and of social dynamics. However, some basic characteristics like the gender of the entrepreneur, the geographical location, or the social context may have a tremendous impact on the possibility to become an entrepreneur, to create a firm and to prosper. This book is a collection of papers written by an array of international authors interested in the question of entrepreneurship from a gender point of view (male vs female entrepreneurship), a geographical point of view (Africa, Europe, America and Latin America, Asia...) or a specific social context point of view (agricultural economy, farming or family business, etc.).